2021
DOI: 10.1093/elt/ccab014
|View full text |Cite
|
Sign up to set email alerts
|

Using metaphor elicitation with pre-primary children learning English

Abstract: This article reports on a study that investigates children’s experiences and perceptions of English language learning by using a metaphor elicitation technique. Giving children a voice in the early years recognizes children as individuals and as active and capable participants in their own learning. It gives both children and teachers an insight into the language learning process and contributes to a more learner-centred pedagogy. Previous studies using this technique have shown that children are creative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The aim is to demonstrate that medals are more helpful in stimulating learners' metaphorical abilities and to further improve the effectiveness of metaphorical information in English language teaching. Literature [13] uses metaphor elicitation techniques to make children realize that a child is an individual and an active and capable participant in their learning. By providing insight into the language learning process for both the child and teacher, it fosters a more learning-centered pedagogy.…”
Section: Related Researchmentioning
confidence: 99%
“…The aim is to demonstrate that medals are more helpful in stimulating learners' metaphorical abilities and to further improve the effectiveness of metaphorical information in English language teaching. Literature [13] uses metaphor elicitation techniques to make children realize that a child is an individual and an active and capable participant in their learning. By providing insight into the language learning process for both the child and teacher, it fosters a more learning-centered pedagogy.…”
Section: Related Researchmentioning
confidence: 99%
“…The use of data analysis in three controlled experiments demonstrated that both native language vowel articulation and English vowel articulation affect static and dynamic spectral features. Literature [9] reported on an investigation into the English learning processes and cognitive programs of children using metaphorical heuristics. Respectfully acknowledging children's independence during early childhood leads to their active participation in learning, which enables them to become more creative and confident.…”
Section: Introductionmentioning
confidence: 99%